Characterization of Canadian Strikes: Some Critical Comments - Smith, Michael R. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1979)
This paper examines examples of two different intellectual traditions within which Canadian strikes are interpreted. The distinctiveness of the two traditions becomes most clear in reactions to a paper by Crispo and Arthurs (1968) on industrial conflict in the mid i960*s. Each tradition involves assumptions about the nature of industrial conflict. In neither of the examples discussed from the two traditions, however, is the adequacy of the assumptions really established. Despite the fact that these two traditions assert entirely contradictory characterizations of Canadian strikes, there appears to be no serious dialogue between the exponents of either position.